2019
DOI: 10.35799/pha.8.2019.29354
|View full text |Cite
|
Sign up to set email alerts
|

UJI AKTIVITAS ANTIBAKTERI NANOPARTIKEL EKSTRAK LENGKUAS PUTIH (Alpinia galanga (L.) Willd) TERHADAP BAKTERI Klebsiella pneumoniae

Abstract: White galangal rhizome (Alpinia galanga (L.) Willd's) scientifically proven has properties as antibacterial, antifungal, anticancer, antitumor, antioxidant and cytotoxic. In nano size, the contact surface area of the particle becomes larger which can increase the amount of active substance which is isolated more so that the antibacterial activity is stronger. This study aims to determine whether the white galangal extract nanoparticles have antibacterial activity against the bacteria Klebsiella pneumoniae and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 2 publications
1
4
0
4
Order By: Relevance
“…This result is in line with the research of Yahya Y. The most important active ingredient in the list of secondary metabolites compounds is flavonoid, potential natural antioxidant due to its ability to eliminate and inhibit the formation of free radicals [17] . Eliminating free radicals is important for anti-cancer activity because an increase in free radicals causes oxidative damage in cells, which is likely to be one of the key mechanisms involved in cancer and some of the other symptoms documented in the scientific literature [12] .…”
Section: Figure 1 Concentrated Extract Of the Bidara Fruitsupporting
confidence: 88%
See 1 more Smart Citation
“…This result is in line with the research of Yahya Y. The most important active ingredient in the list of secondary metabolites compounds is flavonoid, potential natural antioxidant due to its ability to eliminate and inhibit the formation of free radicals [17] . Eliminating free radicals is important for anti-cancer activity because an increase in free radicals causes oxidative damage in cells, which is likely to be one of the key mechanisms involved in cancer and some of the other symptoms documented in the scientific literature [12] .…”
Section: Figure 1 Concentrated Extract Of the Bidara Fruitsupporting
confidence: 88%
“…Bacterial activity is considered weak if the diameter of the inhibition zone is <5 mm, moderate if the diameter is between 5-10 mm, strong if it is between 10-20 mm, and very strong if >20 mm. It could be concluded that the inhibition power of the bidara fruit, which ranged from 12.8-21.1 mm, is strong in a concentration of 12.5 %-75 % and very strong in a concentration of 100% [17] . Based on the result of the organoleptic test, the Juju Jam could be accepted well by 33 panellists.…”
Section: Figure 1 Concentrated Extract Of the Bidara Fruitmentioning
confidence: 97%
“…Cell suspensions can scatter light, and the amount of light scattered is proportional to the number of cells present [28]. The more cells there are, the more scattered light, and the more turbid the suspension will look.…”
Section: Discussionmentioning
confidence: 99%
“…Setelah itu, cangkang telur di oven pada suhu oven 60°C selama 3 jam. Kedua bahan dihaluskan menggunakan mesin penepung lalu disaring menggunakan sieve shak er mesh 100 (Kumowal et al 2019).…”
Section: Pembuatan Tepung Temu Ireng Dan Cangkang Telurunclassified